(untitled) (Bangladesh Journal of Agricultural Research, 2022)
Several management approaches were evaluated against pod borer attacking yard long bean during April - July, 2019 at Entomology Research Field, Bangladesh Agricultural Research Institute (BARI), Gazipur. The management package namely sanitation + spraying bio-pesticide Antario (Package 1), sanitation + spraying bio-pesticide Spinosad 45 SC (Package 3) and sanitation + alternate spraying of Antario and Spinosad 45SC (Package 4) showed almost equal effectiveness in reducing flower and pod damage by pod borer and higher yield. But the management package sanitation + spraying bio-pesticide Antario (Package 1) appeared best as it provided the highest marginal benefit cost ratio (MBCR) (10.09), which was followed by sanitation + alternate spraying of Antario and Spinosad 45SC (6.97) (Package 4), and sanitation + spraying biopesticide Spinosad 45 SC (5.29) (Package 3). The effectiveness of sanitation +Bt kurstaki) (Package 2) was poor in respect of yield (12.06 tha-1) and MBCR (3.44). Bangladesh J. Agril. Res. 45(3): 233-237, September 2020